2016
DOI: 10.1097/jsm.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Single-Leg Squat as a Tool to Evaluate Young Athletes' Frontal Plane Knee Control

Abstract: This file was downloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Räisänen, A., Pasanen, K., Krosshaug, T., Avela, J., Perttunen, J., Parkkari, J. (2015). Tampere University Hospital for financial support of the study. Design: Frontal plane knee control was assessed by a physiotherapist on a three-point scale. Conflicts of interest and sources of fundingFrontal plane projection angles were calculated from video images. To determine the intrarater reliability, a physiotherapist re-asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…The SLS test is used in clinical practice to assess frontal plane knee control. The visual assessment of frontal plane knee control correlates well with the FPKPA, when assessment if performed by experienced observer . Previous studies on young athletes have shown that reduced frontal plane knee control is associated with higher risk of future injuries, although all the studies are not in agreement .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The SLS test is used in clinical practice to assess frontal plane knee control. The visual assessment of frontal plane knee control correlates well with the FPKPA, when assessment if performed by experienced observer . Previous studies on young athletes have shown that reduced frontal plane knee control is associated with higher risk of future injuries, although all the studies are not in agreement .…”
Section: Discussionmentioning
confidence: 79%
“…The SLS test protocol and the 2D video analysis method is based on the work of Stensrud et al and has been described in detail previously . An alteration to the previous protocol was made by cutting out the warm‐up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate individual's risk of sustaining non‐contact LE injuries, different tests to screen athletes’ movement control have been developed. Both two‐ and three‐dimensional motion analysis methods have been utilized to assess tasks such as vertical drop jump, single‐leg drop jump, and single‐leg squat . Already, several biomechanical variables have been studied and linked to injury risk.…”
Section: Introductionmentioning
confidence: 99%